Digitalization of Regional Regulation Enforcement: A Legal Review of the Use of Information Technology by Batam City's Public Order Agency (Satpol PP) - Syamhudi, Tedy; Sakti, Indra; Maileni, Dwi Afni; Riyanto, Agus (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
The advancement of information technology has led to substantial transformations in government, particularly in the enforcement of regional regulations by the Public Order Agency (Satpol PP). The digitalization of regional regulation enforcement exemplifies the application of e-government principles, intended to enhance the efficiency, transparency, and accountability of regulatory enforcement personnel at the regional level. This study aims to examine the legal framework governing the Satpol PP's use of information technology in executing its regional regulatory enforcement duties. The research involved an analysis of pertinent laws and regulations, including Law Number 23 of 2014 regarding Regional Government, Regulation of the Minister of Home Affairs Number 16 of 2023 on Guidelines for the Nomenclature of Regional Apparatuses in Public Order, Security, and Community Protection, as well as associated policies regulating the application of information technology within the regional government framework. The findings of this study are anticipated to enhance the evolution of administrative law in the digital age, specifically in fortifying the legal framework for the enforcement of information technology-based regional regulations. The research findings are anticipated to offer recommendations for regional governments on formulating policies aligned with the principles of good governance, ensuring that digitalization not only expedites law enforcement processes but also safeguards citizens' rights and legal certainty in their execution. Most crucially, this study finds that the legal legitimacy of digital enforcement is conditioned by privacy-compliant governance: when Batam's Satpol PP processes complaint, surveillance, or violation data without sufficiently specific derivative rules on access, retention, and accountability, the efficiency gains of e-government risk colliding with citizens' privacy rights and weakening legal certainty.